Impact of adding aromatherapy to sound intervention on cardiovascular parameters and psychophysiological measures in cancer patients: a randomized exploratory trial - Hohneck, Anna; Troia, Melissa; Kolar, Valentin; Weingärtner, Simone; Merx, Kirsten; Sarodnick, Felicitas; Mavratzas, Athanasios; Burkholder, Iris; Schumacher, Gerhard; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter (Oncology research and treatment, 2025)
Introduction: Integrative therapeutic approaches are able to improve psychophysiological outcomes in cancer patients. Whether additional beneficial effects can be achieved by combining aromatherapy to sound intervention is unclear. Methods: Eighty cancer patients were randomized (1:1) to either a 20-min sound intervention (“sound only,” classical music via headphones) or a sound intervention combined with aromatherapy (“aroma”). Cardiovascular parameters (measured with VascAssist2.0), visual analogue scales for emotional well-being, anxiety, stress, pain and sadness, and the State Trait Anxiety Inventory were assessed before and after intervention. Results:Sound only led to a significant reduction in the heart rate, while a trend for a lower heart rate was observed in the aroma group. Both pulse wave velocity (p = 0.04) and vascular resistance (p = 0.04) were reduced by sound only. Psychophysiological outcomes were improved by both interventions with a more pronounced but not significantly different effect on pain reduction by aroma (aroma p < 0.001; sound only p = 0.002). Conclusion: Both interventions were able to improve psychophysiological outcomes. In terms of cardiovascular parameters, a sound intervention alone achieved greater but not significantly different results compared to aroma, while the addition of aromatherapy yielded no substantial additional effects.
Online veröffentlicht: 4. Juni 2025
Gesehen am 30.09.2025